An intelligent sensing ubiquitous study using cyber and social psychology for group purchase behaviour - Gohel, Payal (INFOCOMP Journal of Computer Science, 2019)
In today’s time, use of social media defines an era where billions of users, everyday uses the power of social media to get empowered. It has the capacity to impact our lives and has opened a new opportunities and possibilities that were not possible. Social networks are fundamentally social tools in which people are constantly observing and growing their social network, most social network media depict growth using the degree of point definition, control and independence. Centrality can also indicate which members are the most useful or well-connected and therefore the best information resources. This research targets the emerging area of group purchasing, social marketing and target advertising. Social marketing will enhance the market understanding by learning what people want and need rather than trying to persuade them to buy what they happen to be offering. This aim of this research is to investigate how the social marketing paradigm works, involve students in the research experiments to educate and train them regarding latest technologies involved, and identifying the approach to do it right. The proposed research successfully implemented android app dubbed as SONET to conduct research experiments and interacted with targeted users. This app focuses on i) user’s privacy related issues, ii) periodical data capturing and iii) user’s localization. Couple of research methods are used in research experiments to conduct qualitative and quantitative data including i) SONET app captures consistent data over time for 4 weeks and helps to build the dynamic datasets of social contact network ii) Conducted online Survey to gather quantitative data from SNS users.